Women's Empowerment in Village Governance Transformation in Indonesia: Between Hope and Criticism. (April 2019) - Kushandajani,; Alfirdaus, Laila Kholid
Since the launch of Law No. 6/2014 regarding villages, scholarly concerns on village studies are growing. However, studies focusing on gender equality in Village Law implementation are still few. This article discusses the responses of the village government to gender problems in their respective areas. Based on field research in two villages in Java, namely Panggungharjo and Lerep, this article recognizes that there is greater attention on gender issues since the implementation of the law. However, village heads still dominate village policymaking. Further, although gaining some supports, gender issues are still placed as the secondary among the village development priorities. They also lack of empowerment programs that will have a direct impact on the improvement of gender equality. Considering these criticisms, there is a crucial need for the national government to issue regulations that will encourage a stronger assertion of gender equality in Village Law implementation.